Evaluation of SmearOFF, maleic acid and two EDTA preparations in smear layer removal from root canal dentin. (2nd January 2019) - Ballal, Nidambur Vasudev; Jain, Himanshu; Rao, Sheetal; Johnson, Alexander D.; Baeten, John; Wolcott, James F.
Abstract: Objectives: To evaluate SmearOFF, 7% maleic acid (MA) and two different preparations of ethylenediaminetetraacetic acid (EDTA) in smear layer removal. Materials and methods: Fifty single-rooted teeth were separated into five groups, instrumented and irrigated as follows: (1) SmearOFF, (2) 7% MA, (3) 18% EDTA (pH 11.4), (4) 17% EDTA (pH 8.5) and (5) 0.9% saline. Teeth samples were blinded and examined by scanning electron microscopy with Image J software. Results: Eighteen percent EDTA was less efficient when compared to SmearOFF and MA at all thirds of the root canal system. There was no difference between SmearOFF and MA in the coronal and middle thirds. In the apical third, MA removed more smear layer. Seventeen percent EDTA was as efficient as SmearOFF and MA in coronal and middle third but not in the apical third. Eighteen percent EDTA removed smear layer less efficiently in the coronal and middle thirds than 17% EDTA; in the apical third, there was no difference observed. In the saline group, all specimens were heavily smeared. There was no significant difference between 18% EDTA and saline at all canal thirds. Conclusions: SmearOFF and 17% EDTA (pH 8.5) had better smear layer removal capability in the coronal and middle thirds of the root canal system. In the apical third, 7% MA was superior. 18% EDTA (pH 11.4) and saline had poor smear layer removal ability.